Ni doping in CuO: A highly sensitive electrode for sensing ammonia in ppm level using lanthanum gallate based electrolyte. (October 2019) - Nithya, S.; Sharan, R.; Roy, Mainak; Kim, Hack Ho; Ishihara, Tatsumi; Dutta, Atanu
Graphical abstract: Highlights: Ni 2+ phase was not observed in XRD analysis for <10 mol% in CuO. Micro raman studies revealed the presence of Ni 2+ from 2 mol% of doping. UV–vis reveals the increase of doping level with decreasing band gap values. With increase of Ni 2+ doping, the morphology of the particles decreases in size. 1 mol% Ni doped CuO showed a high sensitivity of 135.5 μA/decade at 550 °C. Abstract: Ni 2+ doped CuO (Cu1-x Nix O for 0 ≤ x ≤ 0.3) nanocrystalline powders were synthesized by combustion technique. The doped samples were found single phasic from powder XRD for up to 10 mol%, above which precipitation of NiO phase was observed. Raman study however indicated the presence of Cu2 O phase in both undoped and doped samples up to 1 mol% Ni 2+ doping. At and above 2 mol% doping, precipitation of the NiO phase was observed. Morphology of powders got modified drastically upon doping. Band gap showed decreasing trend with the increase of doping concentration in CuO, attributed to the formation of intra-band defect states. XPS revealed the presence of adsorbed oxygen or carbonate species on the surface. For the first time, Ni 2+ doped CuO is reported as catalyst (active electrode) for ppm level NH3 sensing in amperometric mode with high sensitivity of 135.5 μA/decade at 550 °C using LaGaO3 as solid electrolyte.